2017
DOI: 10.1002/bip.22908
|View full text |Cite
|
Sign up to set email alerts
|

MgI2‐chemoselective cleavage for removal of amino acid protecting groups: A fresh vision for peptide synthesis

Abstract: In the field of peptide synthesis, the key to a successful access to synthetic targets lies on a pertinent combination of protecting groups. Their choice is directed by their selective removal conditions. We present here the behavior of some of the most used protecting groups in peptide chemistry under experimental cleavage conditions, combining MgI with MW irradiation, using 2-Me-THF as a green solvent. In these experimental conditions, the benzyloxycarbonyl protecting group as well as the Merrifield resin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The peptide analogue (Lys-Gly) 5 -MOG 35-55 , referred as (KG) 5 -MOG 35-55 , was synthesized using standard peptide chemistry techniques and previously published by our group. Briefly, Fmoc/tBu methodology was used which included 2-chlorotrityl chloride resin (CLTR-Cl) and N a -Fmoc (9-fluorenylmethyloxycarboxyl) side chain protected amino acids [ 43 , 44 ]. The purity of the peptides were shown to be >97% by analytical HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…The peptide analogue (Lys-Gly) 5 -MOG 35-55 , referred as (KG) 5 -MOG 35-55 , was synthesized using standard peptide chemistry techniques and previously published by our group. Briefly, Fmoc/tBu methodology was used which included 2-chlorotrityl chloride resin (CLTR-Cl) and N a -Fmoc (9-fluorenylmethyloxycarboxyl) side chain protected amino acids [ 43 , 44 ]. The purity of the peptides were shown to be >97% by analytical HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…The high resolution of RP-HPLC comes at the cost of higher pressures for rapid separations. We [13,14] and others [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] have reported some applications of high-performance flash chromatography (HPFC) as either the sole purification method or as pre-purification step of crude peptide samples prior to a final HPLC purification step.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that HPFC with normal and reversed‐phase columns can be used successfully for purification of peptides [13–34] . This makes it possible to purify peptides using reversed‐phase column material at a lower pressure and in plastic columns, rather than steel columns.…”
Section: Introductionmentioning
confidence: 99%